Fundamentals of Value versus Growth Investing and an Explanation for the Value Trap. Issue 4 (1st September 2018) - Penman, Stephen; Reggiani, Francesco
Abstract : Value stocks earn higher returns than growth stocks on average, but a "value" position can turn against the investor. Fundamental analysis can explain this so-called value trap: The investor may be buying earnings growth that is risky. Both the earnings-to-price ratio (E/P) and the book-to-price ratio (B/P) come into play. E/P indicates expected earnings growth, but price in that ratio also discounts for the risk to that growth; B/P indicates that risk. A striking finding emerges: For a given E/P, a high B/P ("value") indicates higher expected earnings growth—but growth that is risky. This finding contrasts with the standard convention that considers a low B/P to be "growth" with lower risk. Abstract : A practitioner's perspective on this article is provided in the In Practice piece "Explaining Value vs. Growth Investing through Accounting Fundamentals " by Keyur Patel. Disclosure: The authors report no conflicts of interest. Editor's Note This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. Clifford S. Asness was one of the reviewers for this article. Submitted 12 December 2017 Accepted 23 July 2018 by Stephen J. Brown